Mekanisme Koping pada Remaja di Desa Ragajaya Kecamatan Bojong Gede Kabupaten Bogor - Gusrina Komara Putri; Bunga Ardyani (Politeknik Karya Husada, 2021)
Background: Coping mechanism is the way that individuals do to solving a problem. If the coping mechanism is carried out correctly and successfully overcome the problem, the person would be able to adapt the change or problem. Purpose: This study aims to determine the description of coping mechanisms of adolescents in Ragajaya village, Bojong Gede district, Bogor regency. Method: The research design used by descriptive quantitative design. The sampling technique used by purposive sampling, with a total sample of 285 respondents. The data collected using the Children's Coping Questionnaire (CCQ) questionnaire from the research of Fedorowicz (1995) which has been tested for validity and reliability in a study conducted by Nisak ​​(2017) as many as 35 questions. The analysis used by univariate analysis. Results: The results of the study is using a cut off point with a median value of 88.0, showed that the respondents in this research had maladaptive coping mechanisms as many as 137 adolescents (48.1%), and 148 adolescents (51.9%) had adaptive coping mechanisms. Conclusion: the description of coping mechanisms in adolescents in Ragajaya village, Bojong Gede district, Bogor district, shows that adolescents have more adaptive coping mechanisms.